PENGGUNAAN MEDIA BOOKLET HIV/AIDS TERHADAP SIKAP SISWA KELAS IX DI MTS AL-MASYHURIYAH TENGGARONG SEBERANG - Susi Yulianti; Dwi Hendriani; Nino Adib Chifdillah (Politeknik Kesehatan Kementerian Kesehatan Kalimantan Timur, 2021)
Abstract HIV/AIDS is a global health problem. Efforts to improve attitudes about HIV /AIDS can be done by providing health education. This study analyzed the Influence of Health Education with Media Booklet on HIV/AIDS on The Attitude of Grade IX Students in MTs Al-Masyhuriyah Tenggarong Seberang. The design of this study is a non-equivalent control group design, and the population is grade IX students at MTs. Al-Masyhuriyah Tenggarong Seberang. Sampling techniques total sampling as many as 58 students and divided into two groups, namely the treatment group of 29 students and the control group of 29 students. The results of this study showed the average attitude score of the intervention group increased by 5.7 and the control group by 0.27. There are differences in attitudes in the intervention group between before and after health education interventions with the media booklet to improve students' attitudes about HIV /AIDS media booklet effectively used in the provision of Health Education. Keywords: Booklet, HIV / AIDS, Health Education, Attitude. Abstrak HIV/AIDS adalah masalah kesehatan global. Upaya Peningkatan sikap tentang HIV/AIDS dapat dilakukan dengan pemberian pendidikan kesehatan. Penelitian ini bertujuan menganalisis Pengaruh Pendidikan Kesehatan dengan Media Booklet Tentang HIV/AIDS Terhadap Sikap Siswa Kelas IX di MTs Al-Masyhuriyah Tenggarong Seberang. Desain penelitian ini adalah non-equivalent control group design, dan populasi adalah siswa kelas IX di MTs. Al-Masyhuriyah Tenggarong Seberang. Teknik pengambilan sampel total sampling sebanyak 58 siswa dan dibagi menjadi dua kelompok yaitu kelompok perlakuan berjumlah 29 siswa dan kelompok kontrol berjumlah 29 siswa. Hasil penelitian ini menunjukkan rata-rata skor sikap kelompok intervensi meningkat 5,7 dan kelompok kontrol 0,27. Ada perbedaan sikap pada kelompok intervensi antara sebelum dan sesudah intervensi pendidikan kesehatan dengan media booklet. Sehingga untuk meningkatkan sikap siswa tentang HIV /AIDS media booklet efektif digunakan dalam pemberian Pendidikan Kesehatan. Kata Kunci : Booklet, HIV/ AIDS, Pendidikan Kesehatan, Sikap.